The analysis of giant-slalom and slalom in alpine ski competition - Tadashi, T.; Yuichiro, K.; Keizo, Y. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Alpine ski competitions typically involve different slope types: steep, middle and gentle. Evaluation of the time of each section of a given run aids in elucidating the technical characteristics of the ski competitors. To illustrate, we performed a time analysis of an alpine ski competition, specifically the times for giant-slalom (GS) and slalom (SL) at the 90th All Japan Ski Championships in 2012.